Kapag lumaban ang api
Too much injustice and abuse led to the lost of many lives not to mention the paid support of the police authority that drove Mr. Julio Magsalin (Fernando Poe Jr.) to jail. With clenched fist, he has to come back and fight not only for his family but also for the oppressed and the welfare of their well-loved Samonte Sugar Estate.